Boosting Malaysian graduates’ employability via the new MUET policy. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2015)
Over the last few decades, Malaysia has commenced its effort to propagate the importance of English language as the world becomes increasingly inter-connected digitally and economically where English language proficiency has become a requirement for better employment and opportunities in the global arena. The far reaching effects of the English language as a global language is undeniable in the present digital era and it is crucial that Malaysian graduates have English proficiency to enhance their employability and marketability in today’s era of globalisation. Countries like United Kingdom and Australia are using English as their native language, while Malaysia and India are learning it as second language but China and Korea are embracing it as an international language. In Malaysia, the pressing issue has always been that failure in securing jobs after graduation is related to the inability to communicate effectively in English and a common phenomenon is that one’s success in today’s competitive global world is associated with the mastery of the English language.